1979
DOI: 10.1016/s0022-5347(17)56972-4
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of the Ureter by Small Intestine: Clinical Application and Results of the Ileal Ureter in 89 Patients

Abstract: Partial or total replacement of the ureter by small intestine was performed at the University of California/Los Angeles Hospital and affiliated hospitals 94 times in 92 patients from 1954 to 1978. Indications included recurrent calculi, ureteral stricture, fistula, congenital obstruction of the ureter and ureteral carcinoma with a solitary kidney. A special use has been for undiversion of an ileal conduit. Followup evaluation was possible in 95% of the patients and ranged from 6 months to 23 years. Thirty-six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
3

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(61 citation statements)
references
References 27 publications
3
55
0
3
Order By: Relevance
“…Case reports to retrospective studies support its use, with overall success rates of up to 81% [44,47,59,63,88]. Bacteriuria and vesico-ileal reflux are common, but do not worsen renal function [63,88]. For extensive bilateral ureteric injuries, a segment of ileum can be tailored as a conduit for both kidneys.…”
Section: Ileal Interpositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports to retrospective studies support its use, with overall success rates of up to 81% [44,47,59,63,88]. Bacteriuria and vesico-ileal reflux are common, but do not worsen renal function [63,88]. For extensive bilateral ureteric injuries, a segment of ileum can be tailored as a conduit for both kidneys.…”
Section: Ileal Interpositionmentioning
confidence: 99%
“…This can be used alone or in conjunction with a psoas hitch or anterior bladder wall flap to minimize the segment of ileum used. Reported complications of ileal interposition include obstruction, prolonged mucus formation, stones, recurrent infections and metabolic acidosis [59,63,88].…”
Section: Ileal Interpositionmentioning
confidence: 99%
“…All cases had a ureteric defect that was too long to be repaired using internal urinary tissue and so the decision of ileal ureter substitution was taken to compensate this defect. Ileal ureter replacement became now an established procedure for ureteric reconstruction especially after the urologists gained more experience in bowel surgery (12). Several studies reported encouraging results regarding surgical ou-tcome and renal function (2,10), however common drawbacks were reported mostly attributed to the absorbing and secreting criteria of the involved ileal segment such as hyperchloremic metabolic acidosis and excess mucus production and also to the wide caliber refl uxing ileal ureter with subsequent progressive dilatation, functional obstruction and recurrent UTI (10,13).…”
Section: Discussionmentioning
confidence: 99%
“…Various surgical techniques have been described for the substitution of long ureteric segments, and the most commonly performed is ileal ureteric replacement [1][2][3][4][5][6][7][8]. Although many surgeons have reported a high success rate with ureteric substitution using the ileum, others have expressed scepticism regarding the long-term efficacy and applicability of this approach [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%